Glocalization of Yoruba Omoluwabi Ideology - Ademola O. Dasylva (Yoruba Studies Review)
Omoluwabi, a Yoruba concept of the Ideal persona, is well foregrounded in the Ifa corpus, the full meaning and import of which are either lost or taken for granted. Previous studles have examined the concept of Omoluwabi, investigated its possible source(s) or origin, and explored its philosophy. The present writer has also been privileged, at different forums, to extend the study's frontiers in different directions, including evolving a home-grown theoretical basis for ideologizing the indigenous Yoruba concept. On each occasion, he has come up with additional exciting findings. The present discourse attempts to stretch the horizon of intellection a little further, such that the theoretical basis for interrogating the Yoruba personality using the Omoluwabi concept is guided by revisionist/historicist assumptions since one is dealing with an all-encompassing philosophical hermeneutic that both defines and engages the sociology of life and llving, the prevalent patterned attitude, and values in the indigenous Yoruba society. "Glocalizatlon," in this context, refers to the extent of the local relevance of pmqluwabl and the possibility of its attaining a higher pedestal of global ideological competitiveness. The paper argues that Omoluwabi remains one great ideology in the Yoruba Ifa knowledge systems practice that possesses a capacity for gauging socially approved human relations of global magnitude; there is a plurality of poetics, not just one. The paper succeeds at, among other things, harnessing and streamlining prevlous findings of this writer on Omoluwabi with the current ones, with a view to sharing fundamental cultural information on the subject for the purpose of making it globally acceptable and adaptable. The paper concludes that the Omoluwabi ideology is capable of fostering genuine development, and that its relevance to worldviews, core universal values, and principles naturally compels an acknowledgment of its profundity, as well as ensures the possibility of its assuming a pedestal of universal philosophical and ideological mediation in an apparently troubled world, albeit not without some soft challenges.